2013
DOI: 10.5935/1984-6835.20130080
|View full text |Cite
|
Sign up to set email alerts
|

Quinoxaline 1,4-di-N-oxide Derivatives: Interest in the Treatment of Chagas Disease

Abstract: Resumo: Mais de 100 milhões de pessoas estão em risco de contrair a doença de Chagas. Estima-se que em 2008, mais de 10.000 pessoas morreram devido a esta patologia. Apesar de a doença ter sido descoberta há mais de 100 anos, ainda é preciso encontrar tratamento seguro e eficaz. Portanto, novos fármacos eficazes contra a doença de Chagas necessitam urgentemente serem descobertos. Derivados de quinoxalina apresentam interessantes propriedades biológicas (anti-infecciosa, citotóxica, anti-candida, anti-protozoár… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Knowledge of the redox properties of pharmaceuticals is also of use in studies focusing on developing new methods that allow electrochemically controlled drug release [60]. Moreover, it has been shown that the mechanism of the biological activity of some compounds is influenced by their redox activity [61,62]. Reliable and accurate correlations between the electrochemical properties and the biological activity of pharmaceuticals are still being sought.…”
Section: Electrochemical Profilementioning
confidence: 99%
“…Knowledge of the redox properties of pharmaceuticals is also of use in studies focusing on developing new methods that allow electrochemically controlled drug release [60]. Moreover, it has been shown that the mechanism of the biological activity of some compounds is influenced by their redox activity [61,62]. Reliable and accurate correlations between the electrochemical properties and the biological activity of pharmaceuticals are still being sought.…”
Section: Electrochemical Profilementioning
confidence: 99%
“…One important feature for their biological activities is the presence of both N -oxide functional groups in the pyrazine ring of the basic quinoxaline structure. N -oxidation generally enhances the scope and level of their biological properties [ 1 , 2 , 16 ], and may be important for bioreduction [ 10 ]. It is well-known that some quinoxaline 1,4-di- N -oxide derivatives undergo bioreduction under hypoxic conditions, leading to the formation of a radical capable of cleaving DNA [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Electrochemistry of carbazole compounds is an object of interest mainly because of their applications [19][20][21][22][23] . However, it has been shown that the mechanism of biological action of some biologically active compounds is associated with their redox activity 24,25 . The aforementioned comparisons were expected to lead to solving research problems.…”
mentioning
confidence: 99%